8 - Zouglou et réalités sociales des jeunes en Côte d’Ivoire: DOI: 10.4314/ad.v31i1.22255 - Blé, Raoul Germain (Africa Development, 2006)
How can the youth’s crave for Zouglou music be accounted for ? Why are poli- ticians, the almighty media, and the entertainment industry all inculcating the youth such stupid music? Aren’t they leading the youth to being passive? Aren’t they handing them over to the watchdogs of capital? This text is offering a different explanation. In Côte-d’Ivoire, there is no one single youth; there are rather multiple and differentiated youth. It is not only an object, but also a subject. It is not always irresponsible, as some think. On the contrary, it strongly designs cultural models drawn from its own daily experience. Musical styles, such as Zouglou are part of these models. Zouglou music reflects the life of young Ivoirians, what they expect from the society, and their claimsand contestations.